[63] Traumatic testicular displacement and torsion: A case report and literature review - Jaffar Hussain (Taylor & Francis Group, 2018)
Objective: To report on a case of traumatic testicular displacement (TTD) and torsion, which is a rare consequence of pelvic trauma. Methods: A 34-year-old motorcycle rider who presented immediately following a head-on collision with a car. His past surgical history included bilateral inguinal varicocoele repair. The patient recalled that his genitals collided with a part of the motorcycle before coming off the vehicle. He complained of left-sided groin pain and was found to have an empty left hemi-scrotum, a tender palpable lump in the left suprapubic region, and bruising in the area. A contrast-enhanced computed tomography (CT) scan revealed an empty scrotum and an ovoid structure measuring 5 × 3 × 4 cm in the subcutaneous tissue with an adjacent spermatic cord and surrounding fat stranding. He was immediately transferred to the operating theatre for surgical exploration of the lower abdomen. Results: After anaesthesia, the testis was repositioned into the scrotum and then we proceeded with exploration of the scrotum that revealed a torted left testicle. De-torsion, warm fomentation and orchidopexy of a viable left testicle was performed. He made an uneventful recovery. He was then transferred to a tertiary trauma centre for further management of his injuries. TTD is defined as migration of one or both testicle outside the scrotum. The most common mechanism of trauma is a rapid deceleration straddle injury against a motorcycle fuel tank. Predisposing factors include inguinal hernia repair, wide external inguinal ring, and atrophic testes. Radiological examinations of choice include colour-flow Doppler ultrasonography and CT scans of the abdomen and pelvis. Management consists of either closed reduction of the testicle or surgical exploration. Conclusion: Early diagnosis and management of TTD is imperative to preserve the displaced testicle.